Diabetes and pregnancy, a problem not only for obstetricians and diabetologists - Wender-Ożegowska, Ewa; Zawiejska, Agnieszka (Przewodnik Lekarza/Guide for GPs, 2007)
The discovery of insulin and introduction of insulin preparations into clinical practice created a unique opportunity to treat people suffering from diabetes type 1 successfully. Prior to this success, pregnancy in diabetic women was extremely rare and most cases resulted in stillbirth and fatal outcome for the mother. Since the introduction of insulin in 1923 into therapy of pregnant women with diabetes, a permanent improvement in neonatal and maternal outcome has been noted. However, a diabetic pregnancy still constitutes a high risk pregnancy, requiring targeted, highly specialized monitoring of woman and foetus by physicians of different specializations.